Therapeutic Potential of Resveratrol in Lymphoid Malignancies. (2nd April 2016) - Khan, Omar S.; Bhat, Ajaz A.; Krishnankutty, Roopesh; Mohammad, Ramzi M.; Uddin, Shahab
ABSTRACT: Natural products have always been sought as a dependable source for the cure of many fatal diseases including cancer. Resveratrol (RSV), a naturally occurring plant polyphenol, has been of recent research interest and is being investigated for its beneficial biological properties that include antioxidant, anti-inflammatory, proapoptotic, and growth inhibitory activities. These effects are mainly mediated by cell cycle arrest, upregulation of proapoptotic proteins, loss of mitochondrial potential, and generation of reactive oxygen species. Among the beneficial properties of RSV, the anticancer property has been of the prime focus and extensively explored during the last few years. Although reports exist on the chemopreventive role of RSV in many solid tumors, limited information is available on the antiproliferative activity of RSV in human lymphoma cells and experimental models. Potential mechanisms for its antiproliferative effect include induction of cell differentiation, apoptosis, and inhibition of DNA synthesis. In this review, the different kinds of lymphoid malignancies and the main mechanisms of cell death induced by resveratrol are discussed. The challenges are limiting in vivo experimental studies involving resveratrol. An attempt for the translation of this compound into a clinical drug also forms a part of this review.